2018
DOI: 10.1007/s00737-018-0890-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring female intrasexual competition by the scale for intrasexual competition: a validation of the German version

Abstract: Competitive behaviour amongst members of the same sex is termed intrasexual competition. The tendency to engage in such competition appears to be strongly related to stable individual characteristics such as personality traits. Additionally, recent studies have revealed transient fluctuations in competitiveness according to the female menstrual cycle. To date, no German questionnaire exists to measure intrasexual competition. Our first study aimed to translate and validate the Intrasexual Competition Scale (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The validated German version of Buunk and Fisher's ( 5 ) Scale for Intrasexual Competition was applied ( 5 , 6 ). The questionnaire consists of 12 items which are rated on a 7-point Likert scale ranging from ( 1 ) not at all applicable to ( 7 ) completely applicable (i.e., “I can't stand it when I meet another woman who is more attractive than I am.” “I tend to look for negative characteristics in attractive women.”).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The validated German version of Buunk and Fisher's ( 5 ) Scale for Intrasexual Competition was applied ( 5 , 6 ). The questionnaire consists of 12 items which are rated on a 7-point Likert scale ranging from ( 1 ) not at all applicable to ( 7 ) completely applicable (i.e., “I can't stand it when I meet another woman who is more attractive than I am.” “I tend to look for negative characteristics in attractive women.”).…”
Section: Methodsmentioning
confidence: 99%
“…The Cronbach's alpha in this study was 0.86, suggesting a good internal consistency. As proposed in our validation study, subscales were calculated for the competition on (I) attention and interpersonal success, (II) competence, and (III) appearance ( 6 ). Cronbach's alphas for these subscales were 0.80 for attention and interpersonal success, 0.79 for competence, and 0.75 for appearance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, ISC has been found to be associated with hormones. For example, among women ISC is higher during the late follicular phase compared to the midluteal phase of the cycle (Fiacco et al, 2018), and among men ISC is higher among those high in testosterone (Arnocky et al, 2018). Furthermore, Buunk et al (2014) found that young women were consistently higher in ISC the higher the socioeconomic status of their parents, assumedly because young women are currently on average more highly educated than young men are, intensifying female competition over highly educated men.…”
mentioning
confidence: 99%